HUBUNGAN KOMUNIKASI TEURAPETIK BIDAN DENGAN KECEMASAN IBU BERSALIN DI RSUD KELAS B DR.R. SOSODORO DJATIKOESOEMO BOJONEGORO - LUTHFIA, ERIEN; AZIZAH, NUR (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2016)
ABSTRACT                Therapeutic communication is communication consciously planned, aimed and focused on the patient's recovery. Therapeutic communication leads to a form of interpersonal communication. Therapeutic communication skills is the ability or midwife to help patients adapt to stress, cope with psychological disorders, and learning how to relate to others. Therapeutic communication is interpersonal relationship between the midwife with the patient, in this connection midwife and patient gain a shared learning experience in order to improve the patient's emotional experience.                   This research is an analytic cross sectional approach, conducted at room Midwifery and Maternity Hospital Regional General Bojonegoro from 12 until August 21, 2015. The population in this study were all birth mothers are treated in Obstetrics and Maternity totaled Sigli General Hospital 57. The method of determining the sample in this study was accidental sampling which amounted to 57 respondents. Data collection is an interview using a questionnaire containing 30 questions about communication teurapetik midwives and maternal anxiety levels. The results showed that there is a relationship between midwives teurapetik communication with maternal anxiety levels in the obstetrics and maternity Regional General Hospital Bojonegoro Year 2015 (P value = 0.004).            The final conclusion is that the communication teurapetik performed by a midwife can reduce the anxiety of the mother in childbirth. There needs to be improvement of quality of care in hospitals and the increased capacity of midwives in communication and counseling more optimal, increasing labor companion and complementary facilities that can give rise to positive psychological effect, so as to give a spirit and a sense of calm for mothers.    Keywords: Communication Teurapeti Midwife, Mother Maternity Anxiety